Development of a streamline curvature axial-flow compressor performance simulator graphical-user-interface for design and research - Azamar Aguirre, Hasani; Pachidis, Vassilios; Templalexis, Ioannis (International Society for Air Breathing Engines (ISABE), 2017)
The all-time interest to increase turbomachinery efficiencies and pressure ratios has led to the progression of more robust and accurate simulation methods and tools. Even though 3-D CFD analyses are highly detailed and despite the computational power nowadays, they can be costly in terms of time and resources. Conversely, 2-D SLC methods provide acceptable performance and flow field results in short times. Because of economical and practical reasons, SLC still represents the cornerstone for turbomachinery design. In the present, the knowledge demand from the academia community in the airbreathing engine field has been expanding year after year. Nevertheless, there are very few open-source turbomachinery solvers that can be accessed, where user needs to know at least the basics of the programming language syntax and familiarize with it. For these reasons, a GUI was developed for an existing in-house 2-D SLC axial-flow compressor performance code, called SOCRATES. A GUI in this context supports as a teaching mechanism to explain not only the method itself, but also the compressor aerodynamic behaviour. The SOCRATES GUI consists in the axial-flow compressor model setup, solution and visualization for geometry and results. This paper outlines the main features of the 2-D SLC GUI, and uses a two-stage fan to show the flow field parameters and compressor/fan map, showing a consistent agreement against measured data.
Keywords: Streamline Curvature; Through-flow; Blade Analysis; Blade Design; Compressor; Fan